A radiolarian-based palaeoclimate history of Core Y9 (Northeast of Campbell Plateau, New Zealand) for the last 160 kyr - Panitz, Sina; Cortese, Giuseppe; Neil, Helen L.; Diekmann, Bernhard (PD Dr. habil.) (Marine Micropaleontology, 2015)
Sea-surface temperatures (SSTs) based on radiolarian assemblage changes are estimated for the last 160 kyr, from a sediment core (Y9) recovered from Pukaki Saddle, northeast of Campbell Plateau. Site Y9 lies beneath Subantarctic Surface Water (SAW) immediately to the north of the Subantarctic Front (SAF), which in this region is bathymetrically constrained by the edges of Campbell Plateau and defines the northern boundary of the Antarctic Circumpolar Current (ACC). Radiolarian assemblages are characterised by an exceptionally high abundance of the Antarctic to subantarctic species Antarctissa spp. (up to 68%), especially during glacial intervals. SST estimates are derived using Factor Analysis and the Modern Analog Technique. Both methods capture the glacial-interglacial (G-I) pattern. The SST reconstructions show the changing relative influence of distinct water masses during the past G-I cycle, with major temperature variations of the order of 7-9 degrees C at glacial Terminations. Glacials (marine isotope stages (MIS) 6 and 2) are associated with particularly cool SSTs that are indicative of a more vigorous SAF/ACC and an enhancement of the inflow through Pukaki Saddle and/or frequent development of cold-core eddies at the SAF. By contrast, the influence of warmer waters and relaxation of the ACC during interglacials can be inferred from temperatures slightly warmer (e.g., mid-Holocene) and/or comparable to present day (e.g., MIS 5e). During these intervals, relatively warmer temperatures most likely indicate a higher warmcore eddy activity due to a strengthened Subtropical Front and/or a weakened inflow of cool water through Pukaki Saddle and/or an increased stratification in the Campbell Plateau region. Furthermore, the SST record is characterised by an abrupt warming at ca. 10 kyr (i.e., Termination l), the occurrence of a reversal at Termination I, and a warming event at the end of MIS 4, coinciding with the A4 event in the Byrd ice core. These characteristics, together with the pronounced G-I cycle shown ...